METODE SPATIAL MACHINE ANTARA MENCIPTAKAN KONSERVASI KOMODO DAN MENJALIN KEMBALI SAUDARA SEDARAH LEGENDA PUTRI NAJO DI PULAU KOMODO - Joshua Keefe; Agustinus Sutanto (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2021)
Starting from a happy life where the human settlement and Komodo dragons live side by side. Generation to another generation, the people of Komodo village have believed in totemism from the legend of Princess Najo who gave birth to two male twins, one in the form of a human and one in the form of a Komodo dragon. At that time, humans shared their prey with the Komodo dragons. Now the Komodo village, whose life is in the tourism sector, will be allocated to another island by the government. When the Komodo people are restless, many dragons swim everywhere. There is a flesh and blood relationship between the Komodo dragon and humans. The residents balked and would rather die than have to move from the village which they called their "spilled blood". Plus the threat of a break in the Komodo dragon's food chain due to illegal poaching of Timor deer by illegal communities. The purpose of this research focuses on raising the nobility value of the Komodo village with the existence of the Komodo dragon due to the breaking of the traditional totemism chain and the scarcity of the Komodo dragon. This research uses a spatial machine method which aims to turn on the Komodo dragon's breathing space which is mutualized with the daily life of the village based on the legend of Putri Najo to its original locus in the past. The experience that the author shares is a thought in planning social systems and ecosystems on Komodo Island in response to "Beyond Ecology". A typology of conservation buildings that aims to protect, care for, breed where the Komodo dragon is not just an animal, but is a blood relative. Keywords: Komodo dragon; Putri Najo; Spatial Machine AbstrakBerawal dari kehidupan yang bahagia dimana perkampungan manusia dengan komodo hidup saling berdampingan. Secara turun-temurun, masyarakat desa Komodo memiliki kepercayaan totemisme dari kisah legenda Putri Najo yang melahirkan dua anak kembar laki-laki, yang satu berwujud manusia dan satu lagi berwujud komodo. Pada masa itu, manusia saling membagikan hasil buruannya kepada komodo. Sekarang kampung Komodo yang hidupnya pada sektor pariwisata akan dialokasikan ke pulau lain oleh pemerintah. Ketika orang Komodo gelisah, banyak komodo berenang kemana-mana. Terasa ada hubungan darah daging dan batin antara komodo dengan manusia. Warga menolak keras dan lebih baik mati daripada harus pindah dari desa yang mereka sebut ‘tumpah darah’ mereka. Ditambah ancaman putusnya rantai makanan komodo akibat perburuan liar rusa Timor oleh masyarakat ilegal. Tujuan dari penelitian ini berfokus dalam mengangkat nilai keluhuran desa Komodo dengan keberadaan komodo akibat putusnya rantai tradisi totemisme dan kelangkaan komodo. Penelitian ini menggunakan metode mesin keruangan bertujuan menghidupkan ruang nafas komodo yang bermutualisasi dengan keseharian desa diangkat dari kisah legenda Putri Najo ke lokus aslinya di masa lampau. Pengalaman yang penulis bagikan merupakan sebuah pemikiran perencanaan sistem sosial dan ekosistem di Pulau Komodo sebagai jawaban dari “Melampaui Ekologi”. Tipologi bangunan konservasi yang bertujuan melindungi, merawat, mengembangbiakkan dimana komodo bukan sekadar hewan, tetapi saudara sedarah.